Sodium butyrate in both prevention and supportive treatment of colorectal cancer - Kaźmierczak-Siedlecka, Karolina; Marano, Luigi; Merola, Elvira; Roviello, Franco; Połom, Karol (Frontiers in Cellular and Infection Microbiology, 2022)
Accumulating evidence suggests that selected microbiota-derived metabolites play a significant role in both tumour prevention and supporting treatment of cancer. One of them are short-chain fatty acids (SCFAs), i.e. mainly acetate, proprionate, and butyrate. Nowadays, it is known that butyrate is a key microbial metabolite. Therefore, in the current review we focused on butyrate and sodium butyrate (NaB) in the context of colorectal cancer. Notably, butyrate is characterized by wide range of beneficial properties/activities. Among others, it influences functioning of immune system, maintains intestinal barrier integrity, positively affects the efficiency of anti-cancer treatment, and may reduce the risk of mucositis induced by chemotherapy. Taking into consideration these facts we analysed NaB (which is a salt of butyric acid) and its impact on gut microbiota as well as anti-tumour activity by describing molecular mechanisms. Overall, NaB is available as for instance food with special medical purposes (depending on country’s regulation) and its administration seems to be promising option for colorectal cancer patients.